Quality of BPJS Services at Mitra Sejati Hospital with Importance Performance Analysis (IPA) Method - Pradani, Ellysa; Syahbudi, Muhammad; Silalahi, Purnama Ramadani (Moneter: Jurnal Keuangan dan Perbankan, 2024)
The number of true partner hospitals in North Sumatra Province has increased since 2012 by 288 units to 310 units in 2023. The increasing number of true partner hospital units does not necessarily mean that true partner hospital services are adequate. This research aims to measure the factors that influence consumer satisfaction and to provide technical responses sourced from the Voice of Customer. This research uses a quantitative analysis method that combines the Importance Performance Analysis (IPA) method to determine service quality factors that influence consumer satisfaction and the Quality Function Deployment method is used to provide a technical response. This methodology uses a quantitative approach using the IPA method to show factors that are among the main priorities, namely services related to providing appropriate diagnoses by doctors at true partner hospitals, services related to responses by true partner hospitals to complaints from patients, and service attributes related to the suitability of drugs given by doctors at true partner hospitals. Increasing responses to patient complaints is a top priority that must be carried out by true partner hospitals to increase patient satisfaction. The technical response with the highest priority order is that medical personnel must provide clear answers regarding the treatment the patient is undergoing, and doctors at true partner hospitals must be more careful in administering medication that is appropriate to the patient’s illness.